# -2x=3x^2-1

## Simple and best practice solution for -2x=3x^2-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -2x=3x^2-1 equation:

Simplifying
-2x = 3x2 + -1

Reorder the terms:
-2x = -1 + 3x2

Solving
-2x = -1 + 3x2

Solving for variable 'x'.

Reorder the terms:
1 + -2x + -3x2 = -1 + 3x2 + 1 + -3x2

Reorder the terms:
1 + -2x + -3x2 = -1 + 1 + 3x2 + -3x2

Combine like terms: -1 + 1 = 0
1 + -2x + -3x2 = 0 + 3x2 + -3x2
1 + -2x + -3x2 = 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
1 + -2x + -3x2 = 0

Factor a trinomial.
(1 + -3x)(1 + x) = 0

Subproblem 1Set the factor '(1 + -3x)' equal to zero and attempt to solve:

Simplifying
1 + -3x = 0

Solving
1 + -3x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -3x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = 0 + -1
-3x = 0 + -1

Combine like terms: 0 + -1 = -1
-3x = -1

Divide each side by '-3'.
x = 0.3333333333

Simplifying
x = 0.3333333333
Subproblem 2Set the factor '(1 + x)' equal to zero and attempt to solve:

Simplifying
1 + x = 0

Solving
1 + x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + x = 0 + -1
x = 0 + -1

Combine like terms: 0 + -1 = -1
x = -1

Simplifying
x = -1Solutionx = {0.3333333333, -1}`